Body Temperature Detection System for Malaria Fever Patient Using RFID And Gsm Network - Mohamad Syukri Effendy B. Mohd. Yusof, Mohamad Syukri Effendy (Universiti Teknologi Petronas, 2009)
Malaria fever patients are known to suffer from fever spikes, where the body temperature rise and fall of a sudden. In hospitals, they were treated normally each 4 hours for check-ups where the nurses will check the temperature and the pulses from the patient. Blood sample need to be taken from the patient to confirm the diagnosis of the disease and identify the infectious parasites. For the blood sample to be taken, the ideal condition is when the body temperature of the patient is at the highest level. Experienced doctor will know the certain ideal time when to take the blood from the patient. However, the case is not the same with inexperienced doctors. What makes it worrying is that if they miss to take the blood when the temperature is at the highest level. What makes it even worst is that by missing the ideal time to draw the blood which will slower the diagnosis process, it will be vital to the patient's life. This is where the "Body temperature detection system for malaria fever patient using RFID and GSM network" comes to the picture. The patient will be receiving the quickest treatment as the system will send signals anytime the temperature exceeds the limits. The signals will then notify the nurses through alarm at nurse's station and send via SMS to the patient's doctor.